2017
DOI: 10.1039/c6ra28525b
|View full text |Cite
|
Sign up to set email alerts
|

Design and synthesis of 1,2,3-triazole–etodolac hybrids as potent anticancer molecules

Abstract: A series of novel 1,2,3-triazole-etodolac hybrids (6a-l) were designed and synthesized as potent anticancer molecules. The synthesis strongly relied on Huisgen's 1,3-dipolar cycloaddition between etodolac azide 3 and substituted terminal alkynes 5a-l. The use of CH 2 Cl 2 as a co-solvent with H 2 O increased the reaction rate and provided the corresponding 1,2,3-triazole-etodolac hybrids (6a-l) in excellent yields compared to other organic co-solvent systems. All the compounds were screened for their in vitro … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…An antiproliferative SAR study of 1,2,3-triazole-containing etodolac derivatives 13 (Figure 4, IC 50 : 3.29-10.71 μm, MTT assay) against A549 cells revealed that the phenyl ring is crucial for the activity, and replacement by the naphthyl group results in loss of activity (Kummari et al, 2017). Introduction of substituents into the phenyl ring is generally detrimental to the activity, whereas methyl at the para position could enhance the activity slightly.…”
Section: 23-triazole-containing Indole Derivativesmentioning
confidence: 99%
“…An antiproliferative SAR study of 1,2,3-triazole-containing etodolac derivatives 13 (Figure 4, IC 50 : 3.29-10.71 μm, MTT assay) against A549 cells revealed that the phenyl ring is crucial for the activity, and replacement by the naphthyl group results in loss of activity (Kummari et al, 2017). Introduction of substituents into the phenyl ring is generally detrimental to the activity, whereas methyl at the para position could enhance the activity slightly.…”
Section: 23-triazole-containing Indole Derivativesmentioning
confidence: 99%
“…Based on the best knowledge, ferrocene, xanthone, azine, and triazole bearing compounds have the good anticancer activity, individually. Now, it has been possible that these frameworks were together in the polymer backbone and show the synergic effect.…”
Section: Resultsmentioning
confidence: 99%
“…Kummari et al . have prepared a range of new 1,2,3‐triazole–etodolac hybrids ( 91 ) by this procedure that to a solution of 2‐(1,8‐diethyl‐1,3,4,9‐tetrahydropyrano[3,4‐ b ]indol‐1‐yl)acetic acid ( 88 ) in dry THF at 0 ° C, a stirred solution of LiAlH 4 in dry THF was added and the mixture was stirred at r.t. After completion and purification, compound 89 was produced.…”
Section: 4‐disubstituted‐123‐triazoles As Anti‐cancer Agentsmentioning
confidence: 99%